2006
DOI: 10.2337/dc06-0145
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Syndrome Is Frequent in Klinefelter’s Syndrome and Is Associated With Abdominal Obesity and Hypogonadism

Abstract: OBJECTIVE—Klinefelter’s syndrome is associated with an increased prevalence of diabetes, but the pathogenesis is unknown. Accordingly, the aim of this study was to investigate measures of insulin sensitivity, the metabolic syndrome, and sex hormones in patients with Klinefelter’s syndrome and an age-matched control group. RESEARCH DESIGN AN METHODS—In a cross-sectional study, we examined 71 patients with Klinefelter’s syndrome, of whom 35 received testosterone treatment, and 71 control subjects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
246
3
11

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 278 publications
(279 citation statements)
references
References 39 publications
19
246
3
11
Order By: Relevance
“…It is this amplification and extension of the injurious oxidative environment that may be responsible for the damage seen in the previously mentioned studies. The proposition is supported by Bojesen et al (2006) who concluded that in Klinefelter's syndrome it was the increased prevalence of diabetes (i.e. hyperglycaemia) rather than hypogonadism or the combination of conditions constituting MetS that is likely to play a role in jeopardising spermatogenesis.…”
Section: Discussionsupporting
confidence: 60%
“…It is this amplification and extension of the injurious oxidative environment that may be responsible for the damage seen in the previously mentioned studies. The proposition is supported by Bojesen et al (2006) who concluded that in Klinefelter's syndrome it was the increased prevalence of diabetes (i.e. hyperglycaemia) rather than hypogonadism or the combination of conditions constituting MetS that is likely to play a role in jeopardising spermatogenesis.…”
Section: Discussionsupporting
confidence: 60%
“…The basis of this concept came from increased insulin resistance found in both hypergonadotropic and hypogonadotropic hypogonadism. Patients of un-treated Klinefelter's syndrome, compared with control subjects, showed a significantly higher prevalence of metabolic risk factors (Bojesen et al, 2006). GnRH agonist-treated men with prostate cancer also showed significantly decreased insulin sensitivity (Smith et al, 2006).…”
Section: Insulin Resistance and Autonomic Hyperactivitymentioning
confidence: 99%
“…Recently, a number of studies in men have suggested that low testosterone may be associated with insulin resistance and testosterone replacement may enhance insulin action [21,22,23,24,25]. A recent study has shown that males with prostate cancer treated with a GnRH agonist are at increased risk of diabetes mellitus [26,27].…”
Section: Hypogonadism and Metabolic Syndromementioning
confidence: 99%